(untitled) (Web of Teachers: Inderscience Research, 2025)
This article explores the synecdochic features in tongue twisters, a unique genre of oral folklore in the Uzbek language. Synecdoche, a literary device where a part represents the whole or vice versa, is frequently used in tongue twisters to enhance linguistic creativity and cognitive engagement. By analyzing common structures in Uzbek tongue twisters, this study investigates how synecdoche is applied to compress complex meanings into simple forms. Through linguistic analysis, the article highlights the cultural and linguistic significance of synecdoche in tongue twisters and its role in language learning and memory enhancement.